De-Construction of Handwritten and Electronic Signature Functions as A Means of Achieving Functional Equivalence - Pavel SHUST; Victor DOSTOV; Anna LEONOVA (Communications of International Proceedings, 2021)
Purpose of this paper is to identify core functions of the handwritten signature to align them with the current approaches towards e-signature regulation. The paper suggests that e-signature shall be seen not as an instrument but rather a set of procedures. Approaches to ensuring the functional equivalence of electronic signatures to handwritten signatures are proposed. The role of the distributed ledger technology is also discussed in context of making the e-signature more accessible by the consumers.
Keywords: simple electronic signature; digital signature; blockchain; distributed ledger electronic signature functions; signature expertise.